(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article explores the structural differences in the usage of abbreviations and clippings during simultaneous interpretation from English to Russian in the context of political discourse. By analyzing interpreter strategies and considering linguistic structures, cultural contexts, and real-time constraints, the study reveals distinct approaches to handling English clippings and abbreviations. The findings highlight variations in usage frequency, adaptation strategies, and the influence of political context. This research contributes to the understanding of linguistic strategies in simultaneous interpretation, offering insights for improving interpreter training and enhancing cross-linguistic political communication.